A Properties of Municipal Solid Waste Incineration Fly Ash (IFA) And Cement Used in The Manufacturing of New Inventive Blended Cement - Mohamad Ibrahim, Norlia; Che Amat, Roshazita; Rahim, Nur Liza; Che Sang Beri, Izzatul Nurain; Mohammed, Syakirah Afiza; Ahmad Zailani, Warid Wazien (International Journal of Integrated Engineering, 2022)
Municipal solid waste incinerator fly (IFA) ash is prone to accumulate high concentration heavy metals. Due to the increasing costs to treat remaining fly ash at the landfill, a lot of research has been done to recycle IFA. This study was focusing on the properties of IFA and cement as main raw materials in new inventive blended cement. The properties of blended cement were also being investigated. Properties of IFA and cement were examined through several test which includes density, specific gravity, X-Ray Fluorescence (XRF), Loss of Ignition (LOI) and through Toxicity Characteristic Leaching Procedure (TCLP) test. The density test and LOI test were also being done for the blended cement. From the tests for IFA and cement, it can be found that density the density of fly ash and cement that has been used for this study were found to be 0.76 g/cm3 and 3.67 g/cm3 respectively. Then, the specific gravity of fly ash and cement were 1.69 and 2.98, accordingly. XRF results shows that both materials have highest content of aluminium, silica and iron, as expected. LOI of fly ash and cement were found to be 17.33 % and 12.33 %, respectively. In terms of the leaching rates of heavy metals (Mn, Ni, Cd, Cr, Cu), only Cd leached at rate 2.39 mg/L, which is above the USEPA's regulatory level, 1.0 mg/L. 5 %, 10 % and 15 % of IFA was mixed with cement to produced blended cement. As the density of blended cement, it was found to be 1.12 g/cm3, 1.08 g/cm3 and 1.09 g/cm3 for each of 5 %, 10 % and 15 % of fly ash in blended cement.